"When you were gentiles": specters of ethnicity in Roman Corinth and Paul's Corinthian correspondence - Concannon, Cavan W. (Synkrisis: comparative approaches to early Christianity in Greco-Roman culture, 2014)
Cavan W. Concannon makes a significant contribution to Pauline studies by imagining the responses of the Corinthians to Paul’s letters. Based on surviving written materials and archaeological research, this book offers a textured portrait of the ancient Corinthians with whom Paul conversed, argued, debated, and partnered, focusing on issues of ethnicity, civic identity, politics, and empire. In doing so, the author provides readers a unique opportunity to assess anew, and imagine possibilities beyond, Paul’s complicated legacy in shaping Western notions of race, ethnicity, and religion